2011
DOI: 10.1089/dna.2011.1259
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variants inNOS1andNOS2AAre Not Associated with Progressive Hearing Loss in Ménière's Disease in a European Caucasian Population

Abstract: Hearing loss in Ménière's disease (MD) is associated with loss of spiral ganglion neurons and hair cells. In a guinea pig model of endolymphatic hydrops, nitric oxide synthases (NOS) and oxidative stress mediate loss of spiral ganglion neurons. To test the hypothesis that functional variants of NOS1 and NOS2A are associated with MD, we genotyped three functional variants of NOS1 (rs41279104, rs2682826, and a cytosine-adenosine microsatellite repeat in exon 1f) and the CCTTT repeat in the promoter of NOS2A gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These studies have suggested the link with NOS dysregulation. However, genetic studies in large MD patient cohorts showed that functional variants in NOS1 and NOS2A are not associated with progressive hearing loss in MD (Gazquez et al, 2011;Teranishi et al, 2013). Our results suggest that the link between the NOS pathway, hydrops and MD could be the DGC complex and alterations in the homeostatic stability of the system.…”
Section: Implications For Meniere's Disease In Humansmentioning
confidence: 99%
“…These studies have suggested the link with NOS dysregulation. However, genetic studies in large MD patient cohorts showed that functional variants in NOS1 and NOS2A are not associated with progressive hearing loss in MD (Gazquez et al, 2011;Teranishi et al, 2013). Our results suggest that the link between the NOS pathway, hydrops and MD could be the DGC complex and alterations in the homeostatic stability of the system.…”
Section: Implications For Meniere's Disease In Humansmentioning
confidence: 99%
“…Surprisingly, not only NOS1, but also NOS2A are upregulated in SGNs in a model of endolymphatic hydrops, suggesting that alternatives of these genes may be related to the neurotoxicity and programmed cell death of SGNs in MD. [41] Incremented NO-synthesis is related to the development of ROS-like lipid peroxides, hydroxyl radicals or peroxynitrite (ONOO -). As it is well-known, oxidative stress by ROS may damage mitochondria complexes, deoxyribonucleic acid, lipid membranes, and proteins.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…A candidate gene approach, either by case-control studies or by the sequencing of selected genes, has been used to search genetic markers associated with MD (Table 3 ). These genes include antiquitin [ 60 ], aquaporin 2 [ 61 ], COCH ( coagulation factor C homology ) [ 62 ], potassium channels genes (KCNE1 and KCNE3) [ 63 ], MHC class II genes [ 64 , 65 ], alpha-adducin [ 66 ], heat-shock protein 70 [ 67 ], PARP-1 [ 68 ], PTPN22 [ 69 ], Fc gamma receptors CD32 and CD16a [ 70 ] and nitric oxide synthases type 1 and 2 [ 71 ]. However, none of these genes could be replicated in an independent set of MD patients [ 72 - 74 ].…”
Section: Meniere Diseasementioning
confidence: 99%